2018
DOI: 10.4028/www.scientific.net/msf.925.436
|View full text |Cite
|
Sign up to set email alerts
|

Solidification Chronology of the Metal Matrix and a Study of Conditions for Micropore Formation in Cast Irons Using EPMA and FTA

Abstract: Microsegregation is closely coupled with solidification, the development of microstructure, and involved in the formation of various casting defects. This paper demonstrates how the local composition of the metal matrix of graphitic cast irons, measured using quantitative electron microprobe analysis, can be used to estimate its solidification chronology. The method is applied in combination with Fourier thermal analysis to investigate the formation of micropores in cast irons with varying proportions of compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Such a behavior is also expected for SG iron. For the case of SG iron, recent work by Domeij et al 7 indicates that microporosity becomes visible at about 0.8 to 0.85 fraction solid.…”
Section: Introductionmentioning
confidence: 97%
“…Such a behavior is also expected for SG iron. For the case of SG iron, recent work by Domeij et al 7 indicates that microporosity becomes visible at about 0.8 to 0.85 fraction solid.…”
Section: Introductionmentioning
confidence: 97%
“…It is possible to understand the effect of nodularity on shrinkage by a change in the solidification mechanism, as reported by Domeij. 6,7 He observed that graphite from the CGI eutectic cells lose contact with the remaining liquid as the solidification change to ductile iron solidification, in the later stages of solidification. The loss of contact of CGI graphite with the liquid explains the loss of positive pressure and the shrinkage formation.…”
Section: Introductionmentioning
confidence: 99%